Against the dominant discourse: making a case for groundwater irrigation for poverty alleviation in West Bengal, India - Mukherji, Aditi (2007)
West Bengal is a state of plentiful rainfall and high groundwater potential. It is also one of the poorer states in India. In view of this, many agencies such as RBI and the World Bank have recommended groundwater irrigation as a tool for poverty alleviation. West Bengal had recorded high agricultural growth rates in the early 1990s. Unfortunately, this growth could not be sustained. This paper argues that one of the main reasons for recent stagnation in West Bengal's agriculture is the severe 'energy-squeeze' it is experiencing due to overwhelming dependence on diesel pumps, recent escalation in diesel prices and low rates of rural electrification. This paper argues that the current groundwater related policies have a resource conservation bias because they have been inordinately influenced by the dominant discourse on scarcity and depletion - a discourse which does not hold good in the case of West Bengal - a water abundant state steeped in poverty. In view of this paradox of scarcity amidst plenty, this paper based on primary data from 40 villages and 580 respondents makes a case for deploying groundwater irrigation for poverty alleviation through electrification of irrigation tubewells and continuation of high flat rate tariff. Quite contrary to the received wisdom that electricity subsidies benefit only the rural rich and that metering of irrigation tubewell is the only answer, this paper argues that neither is necessarily true in the case of water abundant eastern India where efficient and largely equitable groundwater markets operate.